Physiotherapy Management of Calcaneal Fracture in a Patient With Schizophrenia: A Case Report From a Psychiatric Hospital in Indonesia - Farahdina Bachtiar; Agustiyawan Agustiyawan; Andy Sirada; Muhamad Alif Fawaz; Padilah Febiyahna; Ariq Muafa Adli; Zulia Akromatul Azizah (Malahayati Nursing Journal, 2025)
ABSTRACT Physiotherapy is essential in addressing physical health issues and supporting recovery in patients with mental illness. This case report presents a physiotherapy intervention for a 32-year-old woman diagnosed with schizophrenia, who sustained calcaneal and lumbar vertebral fractures. She presented with left ankle edema, localized pain, and restricted joint mobility, resulting in reduced functional mobility and limitations in daily activities. While functional and clinical outcomes showed minimal improvement, pain levels decreased following the intervention. Keywords: Physiotherapy, Mental Illness, Schizophrenia, Ankle, Pain